Inhibition of WIP1 phosphatase sensitizes breast cancer cells to genotoxic stress and to MDM2 antagonist nutlin-3 - Pechackova, Sona; Burdova, Kamila; Benada, Jan; Kleiblova, Petra; Jenikova, Gabriela; Macurek, Libor (Oncotarget, 2016)
PP2C family serine/threonine phosphatase WIP1 acts as a negative regulator of the tumor suppressor p53 and is implicated in silencing of cellular responses to genotoxic stress. Chromosomal locus 17q23 carrying the PPM1D (coding for WIP1) is commonly amplified in breast carcinomas and WIP1 was proposed as potential pharmacological target. Here we employed a cellular model with knocked out PPM1D to validate the specificity and efficiency of GSK2830371, novel small molecule inhibitor of WIP1. We have found that GSK2830371 increased activation of the DNA damage response pathway to a comparable level as the loss of PPM1D. In addition, GSK2830371 did not affect proliferation of cells lacking PPM1D but significantly supressed proliferation of breast cancer cells with amplified PPM1D. Over time cells treated with GSK2830371 accumulated in G1 and G2 phases of the cell cycle in a p21-dependent manner and were prone to induction of senescence by a low dose of MDM2 antagonist nutlin-3. In addition, combined treatment with GSK2830371 and doxorubicin or nutlin-3 potentiated cell death through a strong induction of p53 pathway and activation of caspase 9. We conclude that efficient inhibition of WIP1 by GSK2830371 sensitizes breast cancer cells with amplified PPM1D and wild type p53 to chemotherapy.